Mineral resource management: Evaluating mineral resource throughput management - J. O. Claassen; P. G. Laurens (South African Journal of Business Management, 2016)
Mining operations are increasingly challenged to sustain and improve its profitability. Mineral Resource Throughput Management (MRTM) is showing immense promise to become a fit for use mining management and improvement methodology. Research indicated that the three dimensions of MRTM, namely physical and non-physical constraint management, product payability improvement and optimised decision-making are largely based on the theory of mechanistic and organic systems, the theory of constraints and chaos theory. It also enhances best practices in quality and mining operations management. Managing the impact of variable geology (variable ore and ore body morphology), mining (variable and changing process flow chains) and beneficiation (material compatibility) conditions as well as external variables on production within the MRTM context, mainly centres around understanding and predicting the correct flow behaviour of ore (physical and quality) in downstream processes and synchronisation of the total mining value chain.
Keywords: 650